2021
DOI: 10.3389/fonc.2021.628914
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxic Effects of Arsenite in Combination With Gamabufotalin Against Human Glioblastoma Cell Lines

Abstract: Glioblastoma is a fatal primary malignant brain tumor, and the 5-year survival rate of treated glioblastoma patients still remains <5%. Considering the sustained development of metastasis, tumor recurrence, and drug resistance, there is an urgent need for the novel therapeutic approaches to combat glioblastoma. Trivalent arsenic derivative (arsenite, AsIII) with remarkable clinical efficacy in leukemia has been shown to exert cytocidal effect against glioblastoma cells. Gamabufotalin, an active bufadien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…In fact, Dong et al have demonstrated that bufadienolide compounds such as gamabufotalin and bufalin sensitize human breast cancer cells to TRAIL-induced apoptosis (52). We also recently suggested that gamabufotalin could serve as a promising adjuvant therapeutic agent to potentiate therapeutic effect of arsenite in glioblastoma cells (15). The studies on cytocidal effects of conventional anticancer drugs in combination of Helle or Areno are ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In fact, Dong et al have demonstrated that bufadienolide compounds such as gamabufotalin and bufalin sensitize human breast cancer cells to TRAIL-induced apoptosis (52). We also recently suggested that gamabufotalin could serve as a promising adjuvant therapeutic agent to potentiate therapeutic effect of arsenite in glioblastoma cells (15). The studies on cytocidal effects of conventional anticancer drugs in combination of Helle or Areno are ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 93%
“…Bufadienolides are another kind of important effective constituents of cinobufacini, and we also demonstrated that active bufadienolide compounds such as gamabufotalin, hellebrigenin (Helle) and arenobufagin (Areno) exhibited selective cytocidal effects against intractable cancer cells (12)(13)(14). Furthermore, we recently demonstrated that clinically achieved concentrations of trivalent arsenic derivative (As III ) combined with gamabufotalin exhibited synergistic cytotoxicity against glioblastoma cell line U-87, whereas showed much less cytotoxicity to human normal peripheral blood mononuclear cells (PBMCs) (15). These findings thus provide fundamental insight into the mechanisms underlying the anti-inflammatory and anticancer activity of cinobufacini.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations